Menerapkan Tingkahlaku Anak Dengan Teori Kognitif Serta Mendukung Belajar Melalui Youtube - Aisyah Rahma Saragih; Berlianti (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Behavior is everything that is said or done by someone in the form of actions that can be measured, noticed and assessed, then an act that is done consciously or not. Cognitive theory is an indirect means of measuring what is seen as a very important factor in behavior. The cognitive approach describes that an individual's behavior is very dependent on the way the individual recognizes social situations. In addition, the behavioral influence of cognitive theory also supports children in learning through Youtube media, making it easier for children to repeat lessons that have been taught at school. Based on the case that I observed at the Ora Et Labora Nusantara Orphanage, there was a child who needed help in the form of support to increase self-confidence in learning and behaving towards the surrounding environment. In this Practicum I I provide assistance in the form of stages including the Engagement, Intake, Contract, Assessment, Planning, Intervention, Evaluation, and Termination Stages. The main purpose of Practicum I is to provide solutions to client problems by applying child behavior with cognitive theory and supporting learning through YOUTUBE media.